Effectiveness of Group Guidance Using Finger Painting Games To Improve Social Interaction Among Children with Special Needs in Inclusive Schools - Siti Musdaliva; Munifah Munifah; Dian Fitiriani; Ikhlas Rasido (MASI Mandiri Edukasi, 2025)
This study aims to evaluate the effectiveness of group counseling using finger painting games to improve the social interaction of children with special needs (ABK) in inclusive secondary schools. A mixed-methods approach was used, combining quantitative analysis (Wilcoxon Signed-Rank Test) and qualitative analysis (observations and interviews). The participants were seven students categorized as borderline. Quantitative results demonstrated a significant increase in social interaction scores (p < 0.05), which was supported by qualitative observations of increased cooperation, communication, and participation. The findings suggest that incorporating finger painting activities into group counseling offers a fun, creative, and effective approach to enhancing social interaction among children with special needs in inclusive settings.